Referral of Thyone neofusus Deichmann, 1941, Thyone adinopoda (Pawson & Miller, 1981 and Havelockia obunca (Lampert, 1885) to the genus Sclerothyone Thandar, 1990, and a replacement name for the preoccupied genus Neothyone Deichmann, 1941 (Echinodermata: Holothuroidea: Dendrochirotida) - Thandar, A. S.; Arumugam, P. (Zootaxa, 2022)
Thyone neofusus Deichmann, 1941, Thyone adinopoda Pawson & Miller, 1981and Havelockia obunca (Lampert, 1885) are referred to the genus Sclerothyone Thandar, 1989, and a taxonomic key is provided to all species currently contained in the family Sclerothyonidae Thandar (sensu Smirnov 2012). Since the nomen Neothyone in the family Thyonidae (sensu Smirnov 2012), is preoccupied [(having been used by Hampson (1914) for a group of moths belonging to the family Arctiidae)], the name Lisacucumis nomen nov. is here proposed, with Stolus gibber Selenka as type species, as designated for Neothyone by Deichmann (1941).